Bioinoculants and biochar for sunflower growth promotion in a minig soil - Godinho, Mariana Sofia Brandão (2018)
Soil contamination is a present-day worldwide concern due to the contribution of numerous anthropogenic activities, such as mining activities. The disposal of mine tailings along with deterioration of soil properties can generate several environmental and health problems, thus leading to metal contamination of extensive areas. Borralha mine was one of the biggest producers of tungsten in the past century, until its deactivation. Energy crops, such as sunflower can grant added value to this area since it integrates soils with high levels of metals. Therefore, PhytoSUDOE project intends to restore these contaminated sites, through the implementation of phytoremediation techniques, in order to stimulate ecosystem functionality. Microbial inoculants such as Plant Growth Promoting Rhizobacteria (PGPR) and Arbuscular Mycorrhizal Fungi (AMF) can enhance phytoremediation efficiency through enhanced plant growth, when exposed to stress conditions (e.g. metal contamination). On the other hand, the application of organic soil amendments, like biochar (BC) can influence soil pH, water retention, and nutrient maintenance. Through its adsorption capacity towards metals, it can also reduce the levels of these contaminants and consequent bioavailability in contaminated soil. The main objective of this work was to evaluate the potential of BC amendment and application of microbial inoculants to perform as phytoremediation assistants, for plant growth promotion, specifically for sunflower plants grown in a mining metal-contaminated soil. Sunflower seedlings were inoculated with the bacteria Pseudomonas reactans (B), a commercial AMF (F) and with a mixture of P. reactans and AMF (Mix) grown in a mine soil amended with four percentages of BC (0, 2.5, 5 e 10% (w/w)). Increasing BC levels induced a generic reduction of plant biometric parameters, although inoculation (particularly F and mixed inoculation) had a positive influence on these parameters, since they increased significantly biomass production and balanced nutrient uptake, thus reducing the harmful effects of metals on sunflower growth. Cu accumulation in plant tissues was generally higher in roots than in shoots. BC addition at 2.5 and 5% induced average increases of 28 and 29% respectively, when in comparison to Cu content in roots. However, higher levels of Zn were recorded on sunflower shoots than on roots, as well as N and P contents. The bacterial communities present in rhizospheric samples was analyzed by amplifying 16S rRNA gene fragments, which were separated by DGGE (Denaturing gradient gel electrophoresis). In general, the bacterial communities varied in accordance with the microbial inoculant, where the AMF inoculation appeared to have a higher influence on the bacterial soil communities. This work demonstrates the potential of combining BC and bioinoculants in order to promote sunflower growth in metal contaminated soils and their potential for implementing different phytomanagement strategies.